2015
DOI: 10.11604/pamj.2015.21.53.6727
|View full text |Cite
|
Sign up to set email alerts
|

Morocco’s policy choices to achieve Universal health coverage

Abstract: Morocco's health system remains weak in spite of the improvement of other development indicators in the last ten years. Health remains one of the major challenges to lower the social disparities that are the priority for the authorities. Despite the goodwill of all stakeholders, significant reforms implemented respond only partially to the needs of the population. Morocco established several public insurance schemes, of which one focuses on the poorest, to achieve financial-risk protection for its population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…RAMED is a new national health insurance scheme in Morocco that aims to protect the most vulnerable populations from health‐related out‐of‐pocket expenses. It provides exemption from payment for a wide range of services, including vaccination, reproductive, maternal, newborn and child health, dental and reconstructive surgery, access to medications, treatment and to emergency care . Total health insurance coverage, including RAMED and other schemes covering the formal sector and retirees, was estimated at 53% of the population .…”
Section: Introductionmentioning
confidence: 99%
“…RAMED is a new national health insurance scheme in Morocco that aims to protect the most vulnerable populations from health‐related out‐of‐pocket expenses. It provides exemption from payment for a wide range of services, including vaccination, reproductive, maternal, newborn and child health, dental and reconstructive surgery, access to medications, treatment and to emergency care . Total health insurance coverage, including RAMED and other schemes covering the formal sector and retirees, was estimated at 53% of the population .…”
Section: Introductionmentioning
confidence: 99%
“…The Moroccan government spends 6.5 percent of GDP on health, which is also significantly higher than what the Cameroon government spends. The Moroccan government also offers a national insurance program that covers free immunizations, reproductive, maternal, and child health, as well as dental and reconstructive surgeries to the poor and underprivileged in order to reduce out-of-pocket health costs (33). Other African countries included in table 1 have low UHC-SCIs due to a lack of cash, poorly executed policies, religious and language diversities and over reliance on foreign subsidy to fund their health agendas.…”
Section: Universal Health Coverage-service Coverage Indexmentioning
confidence: 99%
“…The study showed UHC brought hope to improve welfare of the poor (Yilma et al, 2015;Korenman et al, 2016;Ridha & Perdana, 2015;Lu et al, 2020). Nevertheless, the application still faces many challenges (Tinasti, 2015;Yang, 2018), especially for vulnerable populations (Vilcu, 2016).…”
Section: Introductionmentioning
confidence: 99%